KAJIAN KARYA-KARYA ULUM AL-QUR’AN DI INDONESIA DARI TAHUN 2009- 2017 - Muhsin Muhsin (SYAHADAH : Jurnal Ilmu al-Qur'an dan Keislaman, 2018)
This study originated from the words of Ramli Abdul Wahid who said "That the development of the works of 'ulu> m al-Qur'an in Indonesia is slow, because there are still many lecturers who use Arabic-language references" therefore this study aims to prove whether the works of Ulum al-Qur'an in Indonesia are many or not. This can be seen from the number of works ‘Ulum al-Qur'an produced year on year. Therefore, the authors limit this research from 2009 to 2017. Previous studies have been conducted by the author himself in the author's thesis entitled "Bibliographic Study of the works of" Ulum al-Qur'an in Indonesia from 1953 to 2008 ". This study uses bibliographic methods to explain the contents of the book and the reason for writing the work. To get these works, the author will collect based on library catalogs throughout Indonesia and collected based on the year of manufacture, from 2009 to 2017. This research will conclude the number of works of "Ulum al-Qur'an" made by Indonesians.